Assessment of the information competences in the study programs at The University of Zagreb - Banek Zorica, Mihaela (Array, 2014)
Paper presents results of the research of the University of Zagreb study programs and the occurrence of information literacy competences in them. Authors state that there is an overlap between generic and information literacy competences students are expected to acquire upon completing a particular study program and upon completing particular courses which should be stated in the study programs. Both qualitative and quantitative methods were used in analysis and mapping of the data gathered in analysis of the: European framework, generic competences, employability competences and information competences and generic information competences in the study programs. The results of have shown that there is no general approach to the issue but a partial incorporation of information competences in the study programs. Content oriented towards development of information competences is offered partially, usually based upon enthusiasm and individual effort of the teaching staff or information specialists. Even more, these efforts are not based upon clearly defined measurable and comparable learning outcomes. Based on the gathered results authors propose a systematic approach via building the taxonomy of the relevant and measureable learning outcomes, primarily from the employability viewpoint, which will be able to integrate in the study program